A modern view on tubeless percutaneous nephrolithotomy - S. O. Vozianov; A. I. Sahalevych; A. I. Boiko; F. Z. Haiseniuk; V. V. Kohut; B. V. Dzhuran; M. D. Sosnin (Zaporožskij Medicinskij Žurnal)
Urolithiasis ranks second among urological diseases, after inflammatory processes, and first among surgical interventions in urological hospitals. The problem of this disease treatment is a long-term rehabilitation and disablement, which entails a significant increase in costs and requires changes in the tactics of treatment of patients. Since its introduction until today, percutaneous nephrolithotomy (PCNL) is the standard treatment for nephrolithiasis with a stone size of more than 1.5–2.0 cm. In its standard version, PCNL ends with the placement of nephrostomy catheter through the formed parenchymal channel, but there are techniques of the surgery completion either without nephrostomy catheter with a JJ stent – tubeless PCNL, or without nephrostomy and JJ stent at all – totally tubeless PCNL. However, nowadays, the use of tubeless and totally tubeless techniques is one of the most controversial topics in percutaneous nephrolithotomy in terms of safety and efficacy in their application.